(untitled) (Global Journal of Science Frontier Research, 2014)
Three plants, parts used, by the Ogiek community as medicines were collected from Marioshoni in the Mau Forest Complex in the Rift Valley of Kenya, idenfied at the National Museums in Nairobi; S. biflora Voucher No.AO/08/12/12/2006 L. javanica O/015/NMK/06/12/2007 T. asiatica Voucher No. AO/017/NMK/04/07/2007. Each plant species was steam distilled individually. All yielded oils that were separately assayed against some known pathogens that inflict maladies in humans. The two species showed some markable antimicrobial activities for instance, S. biflora was effective against S. aureus, K. pneumoniae and E. coli including all their drug resistant strains. The essential oils from all the three plant species possessed activities against all the strains of S. aureus, different zones of inhibitions L. javanica is amongst other medicinal essential oils that have been studied elsewhere and proved useful medically. However, S. biflora which has varied activities when screened in the laboratory in vitro has not been studied exhaustively. The plant oil extracts gave promising results against both Gram-ve and Gram +ve bacteria. T. asiatica showed good activities against the bacteria and some known pathogenic fungi Further studies on wet bench chemistry and GC showed known classes of compounds which are of known medicinal values were present. It was recommended that further studies be done to ascertain if they can be used as phytomedicine or as components of current allopathic drugs.